THE ROLE OF ISLAMIC INHERITANCE LAW IN WEALTH DISTRIBUTION AND SOCIAL WELFARE - Mahfuz, Mahfuz; Anim, Sarbini; Jiwanto, Fahmi Islam; Geun, Ali An Sun; Maarif, Samsul; Kohari, Khalis (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This study examines the economic and social impacts of Islamic inheritance law (faraidh) on wealth distribution and its adaptation to the modern context. Employing a qualitative approach with observation and literature review, the research explores how faraidh affects economic and social justice, and its capacity to adapt to evolving social and cultural landscapes. Findings indicate that while Islamic inheritance law plays a crucial role in fostering economic and social justice, its effectiveness is often hindered by a lack of understanding, delays in distribution, and family disputes. The study emphasizes the potential of technology and enhanced inheritance law education to mitigate disputes and improve compliance. It recommends a greater role for scholars in providing guidance and the need for a strengthened legal system. Further research should explore the impact of technology in inheritance management, conduct case studies of law implementation in various communities, and evaluate the role of ulama and the impact of inheritance law education on legal compliance.